PENERAPAN PRINSIP-PRINSIP ASURANSI SYARIAH DI INDONESIA DALAM PERSPEKTIF Al-QURAN DAN SUNNAH - Restika, Restika; Taufiq, Muhammad (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2023)
This study discusses the application of sharia insurance principles in Indonesia from the perspective of the Qur’an and Sunnah. Problems with conventional insurance, which in recent years have affected public trust, have recently begun to cause an increase in insurance. Starting from acts of corruption to conditions where insurance companies fail to pay customers, they create a negative image of the insurance climate in Indonesia. The negative image not only affects the image of conventional insurance but also affects the sharia insurance business. In addition, until now, there have been still differences among the public regarding Islamic law regarding sharia insurance, even though there are already rules and fatwas from the National Sharia Council of the Indonesian Ulema Council under number 21/DSN-MUI/IV/2001. This research is descriptive qualitative research using data collection techniques through interviews, observation, and documentation. And the data were analyzed through Miles and Huberman's qualitative data analysis techniques. This study found that there are three principles applied in Islamic insurance policy in Indonesia: al-khidmah (service), at-taawun (help), and al-amn (security). These three principles have not been implemented optimally due to the massive socialization of these policies to the public, weaknesses in human resources (HR), and technology that is not yet very good